Bosnian Croats in Croatia: 'Etnically Privileged Migrant, 'Culturaly Distant Co-ethnics' or 'Croats as any Other Croats'?' - Valenta, Marko (Array, 2011)
Based on previous studies on Bosnian refugees around the world, the authors assume, that unlike other migrants in Croatia, Bosnian Croats in Croatia may be seen as 'co-ethnic migrants' or 'ethnically privileged migrants'. However, it is also assumed that Bosnian Croats in Croatia are defined in two diametrically different ways - as lw status, culturally distant co-ethnics and as Croats as any other Croats, which has resulted in a different positioning toward the mainstream society.